The Role of Social Media Advertising in Shaping Consumer Patronage in Abuja: A Study of MTN - Adeoye, Busayo Olayemi (Darul Yasin Al Sys, 2025)
This study investigates the role of social media advertising in shaping consumer patronage in Abuja, Nigeria, with a focus on MTN’s advertising strategies. Guided by the technological determinism theory, the study sought to determine whether MTN’s social media advertising creates adequate awareness of its products and services and whether it effectively inspires consumer patronage. A survey research design was employed using an online questionnaire administered to a sample of 384 respondents. Findings revealed that respondents are widely exposed to social media, and MTN’s social media advertising successfully creates awareness of its products and services. The advertisements were also found to significantly influence consumer patronage, with Facebook emerging as the most effective platform in inspiring consumer engagement, although its effectiveness was rated at an average level. The study concludes that MTN’s social media advertising is effective in both awareness creation and driving patronage, thereby positioning social networking sites as crucial tools for brand competitiveness in Nigeria’s telecommunications sector. It recommends that advertising agencies and companies adopt Facebook as a primary channel for social media advertising while also exploring other platforms to maximize reach and effectiveness.